A turn-on fluorescent probe based on coumarin-anhydride for highly sensitive detection of hydrazine in the aqueous solution and gas states. (23rd January 2017) - Wu, Guangfu; Tang, Xin; Ji, Wengang; Lai, King Wai Chiu; Tong, Qingxiao
Abstract: In this paper, a new coumarin-based fluorescent probe for hydrazine was rationally designed and successfully synthesized based on the Gabriel reaction. This novel probe enabled highly sensitive and selective detection of hydrazine. The detection limit was 43.6 nM (1.49 ppb). It displayed distinct changes in the intensity of both absorption and emission spectra upon the addition of hydrazine and remarkable color changes can be visually observed. The sensing mechanism of this probe toward hydrazine was characterized by 1 H NMR and mass spectroscopy. Moreover, with the help of theoretical calculations, the sensing capability of this probe for hydrazine detection was described: the electron structure was modulated by a three-substituted group of coumarin once upon the addition of hydrazine. In addition, a test paper experiment indicated its great potential in environment monitoring.